A developmental model of addictions: integrating neurobiological and psychodynamic theories through the lens of attachment. Issue 6 (2nd November 2019) - Alvarez-Monjaras, Mauricio; Mayes, Linda C; Potenza, Marc N.; Rutherford, Helena JV
ABSTRACT: Although substance use and abuse may impact brain and behavior, it is still unclear why some people become addicted while others do not. Neuroscientific theories explain addiction as a series of between- and within-system neuroadaptations that lead to an increasingly dysregulating cycle, affecting reward, motivation, and executive control systems. In contrast, psychoanalysis understands addiction through a relational perspective wherein there is an underlying failure in affect regulation, a capacity shaped early developmentally. Considering recent findings suggesting the neurobiological overlap of addiction and attachment, it may be possible to integrate both perspectives into a developmental model through the lens of attachment. The goal of the present review is to evaluate the value of neurobiological and psychodynamic perspectives to inform our understanding of addiction, particularly substance-use disorders.